Dual-Source Optimization of the "Diverting Water from the Yangtze River to Tai Lake (DWYRTL)" Project Based on the Euler Method. (4th August 2020) - Xu, Ruichen; Pang, Yong; Hu, Zhibing; Kaisam, John Paul
Abstract : Appropriate water body diversion can improve the water quality of Tai Lake. Excessive diversion of water would, however, dramatically alter the local flow fields, which are not conducive to the growth of aquatic plants and the stability of ecosystems. The current "Diverting Water from the Yangtze River to Tai Lake (DWYRTL)" project uses a single water source, the Wangyu River, for diversion, a model that may significantly affect the nearby flow rate or uniformity of the lake and is not conducive to the long-term stability of the aquatic ecosystem in the Tai Lake district of the eastern part of the lake. In order to simulate the different situations of single- and dual-source water diversions (Wangyu-Xinmeng Rivers) in Tai Lake, we based this study on a three-dimensional hydrodynamic model coupled with the Euler method, which can accurately calculate the water exchange rates in the different districts of Tai Lake. The results show that (1) it is recommended that the total annual diversion of water should not exceed 20 × 10 8 m 3 ; (2) the wind field is the most important factor determining the distribution of spatial water exchange; (3) under wind-free conditions, the flow rate of a single-source diversion of water is approximately 50% higher than that of dual-source diversion; and (4) water diversion under the prevailing conditions of the northwest wind in winter will reduce the semiexchange period of the eastern part of the lake area from 50 to 30 days, significantly changing the nearby district's uniformity, leading to ecological risks. Therefore, it is recommended that the dual-source water diversion mode be used in winter and windless season, and single-source water diversion mode be used in other seasons.